ACESSIBILIDADE LINGUÍSTICA EM CENTROS DE EDUCAÇÃO INFANTIL DE TRÊS LAGOAS/MS: UM ESTUDO A PARTIR DO PROJETO POLÍTICO PEDAGÓGICO E DAS PERSPECTIVAS DE PROFESSORES - Claudinéia da Silva (2025)
The teaching of the Brazilian Sign Language (Libras) contributes to the construction of a school for all, which in turn aims at building an inclusive society. As a teacher in the municipal education network of Três Lagoas, Mato Grosso do Sul, this researcher observed that, although there is a municipal law mandating the adoption of measures to include Libras in the school curriculum, there are still persistent difficulties regarding the effective implementation of its teaching in Early Childhood Education Centers (CEIs). This observation motivated the development of the following research question: How have the CEIs in the municipality of Três Lagoas been working to incorporate Libras into their curricula? The general objective of the research was to understand how these centers have promoted—or organized themselves to promote—linguistic accessibility through Libras, as well as to identify the main challenges faced in this process. The investigation was grounded in theoretical frameworks related to school inclusion and linguistic accessibility for deaf children, and it sought to present an overview of the regulations governing special education and the teaching of deaf students, linking these guidelines to elements that foster child development in the initial stage of basic education. Data collection occurred in two stages: analysis of the Pedagogical Political Projects (PPPs) of two CEIs indicated by the Municipal Department of Education (SEMEC), and the conduction of discussion groups with teachers in charge of Group 5 classes. Data analysis was guided by thematic axes predefined based on the specific objectives of this research, namely: (1) Organization of pedagogical work; (2) Conceptions of school inclusion; and (3) Practices aimed at linguistic accessibility. The results revealed that linguistic accessibility for deaf children is still at an early stage in the CEIs, with significant challenges to the integration of Libras into the curricula. It was also possible to understand the conceptions of inclusion expressed by teachers and the pedagogical practices that support them. It was therefore concluded that, although there is a recognized understanding of the importance of Libras for inclusion, the CEIs analyzed have not yet structured, in a planned and organic way, its incorporation into pedagogical practices that effectively promote the linguistic accessibility of deaf children.